Longitudinal association between panic disorder and health care costs in older adults. Issue 12 (14th October 2019) - Hohls, Johanna Katharina; König, Hans‐Helmut; Heider, Dirk; Brenner, Hermann; Böhlen, Friederike; Matschinger, Herbert; Saum, Kai‐Uwe; Schöttker, Ben; Haefeli, Walter Emil; Hajek, André; Wild, Beate
Abstract: Background: To analyze whether probable panic disorder (PD) is associated with health care costs in older age over time. Methods: Data regarding individuals aged 65 and over were derived from two waves of the ESTHER cohort study ( n t1 = 2, 348, n t2 = 2, 090). Probable PD was assessed using the panic screening module from the Patient Health Questionnaire. Health care costs were obtained through monetary valuation of self‐reported health care use data. Fixed effects regressions analyzed the association between transitions in probable PD status and change in health care costs, while adjusting for potential confounders. Results: On a descriptive level, study participants with a positive PD screening displayed higher three‐month health care costs compared to those without (incremental costs: € 259 for t 1, € 1, 544 for t 2 ). Transitions in probable PD were associated with an approximate increase of 65% in outpatient health care costs ( β = 0.50, p < .05). There was no significant association between probable PD transition and change in any other cost category. Conclusions: Using longitudinal data, our results highlight the economic consequences of probable PD in older adults. Future research should address whether reducing PD in older adults may reduce the associated economic burden and analyze underlying mechanisms.